Peningkatan Stabilitas Fisik dan Penerimaan Sensoris Es Krim Fermentasi Fungsional melalui Fortifikasi Mangga: Improvement of Physical Stability and Sensory Acceptance of Fermented Functional Ice Cream through Mango Fortification - Muhammad Tegar Fernanda; Nyayu Karina Katherine; Adinda Marsela; Syerina Raihatul Jannah; Rani Revina Putri; Nancy Eka Putri Manurung (Jurnal Teknologi dan Mutu Pangan, 2026)
Ice cream is an innovative product made from cow’s milk that is widely favored by the public. One form of innovation in ice cream products is the incorporation of probiotic beverages, enabling the product to function as a functional food. This study aimed to analyze the effect of adding mango fruit at different concentrations on the physical properties and sensory acceptance of ice cream. The study employed a Completely Randomized Design (CRD) with three treatments: 0% mango (F1); 25% mango (F2); and 50% mango (F3), followed by fermentation using a fermented beverage containing Lactobacillus casei Shirota as the starter culture which were analyzed using ANOVA followed by Duncan’s multiple range test. The results showed that the addition of mango significantly reduced the overrun value from 75% (F1) to 40% (F3), while extending the melting time from 12 minutes and 1 second (F1) to 39 minutes and 52 seconds (F3). The pH value increased from 4 (F1) to 5 in the mango-containing formulations (F2 and F3). Sensory evaluation indicated that F1 had the best color and texture. In conclusion, the addition of mango improved the physical stability (melting time) and modified the sensory profile of fermented ice cream, but did not significantly alter the overall panelist preference. These findings are expected to serve as a basis for developing functional food products well accepted by the public.